THE EFFECT OF ALBUMIN AS EGG SHELL COATING AND STORAGE TIME ON THE QUALITY OF CHICKEN EGGS - N., Febrianti; Okarini, I. A.; Suranjaya, I G.; Sumadi, I K.; Wijana, I W. (Jurnal Peternakan Tropika, 2021)
The purpose of this study was to determine the effect of albumin as coating an egg shell and shelf life on the quality of eggs consumed during storage. The method used in this study was a Completely Randomized Design (CRD) factorial 4 × 3. The first factor was the treatment of eggshell coating using albumin, consisting of: A1 (control), A2 (thick albumin), A3 (liquid albumin), and A4 (mixed albumin). While the second factor is the treatment of storage time, consisting of: B1 (10 days), B2 (20 days) and B3 (30 days). Each treatment was repeated 3 times and each replication used 3 eggs, with a total of 108 eggs used. The variables observed included changes in egg weight loss, haugh unit, egg yolk index and pH.  The data obtained were analyzed using Analysis of Variance (ANOVA), if there was a significant difference, it was continued with Duncan's Multiple Distance Test. The results of this study indicate that coating fresh chicken eggshells with albumin can maintain the quality of chicken eggs during storage in terms of haugh unit, egg yolk index and pH (P<0.05) and there is no interaction between eggshell coating with albumin and shelf life on quality. eggs (P>0.05).   Key words: albumin, egg quality, storage time